Graphene heat-conducting film and preparation method thereof

By using segmented heat treatment and intercalated graphite paper, combined with the use of polyimide and flake graphite, the problem of film expansion and tearing during the thermal reduction process of graphene thermal conductive film was solved, improving thermal conductivity and product stability, and enabling reliable industrial production.

CN120987303APending Publication Date: 2025-11-21GUANGDONG MORION NANOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411093141.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

During the preparation of graphene thermal conductive film, the removal of functional groups and release of gas during the thermal reduction of graphene oxide film causes the film to expand, resulting in uncontrollable film thickness and easy tearing, which affects thermal conductivity and product stability.

Method used

By employing segmented heat treatment and intercalated graphite paper, combined with the use of polyimide and flake graphite, and by controlling the viscosity and particle size of the graphene oxide slurry, the heat treatment pressure is optimized to avoid membrane expansion and tearing, enhance inter-membrane bonding, and improve thermal conductivity.

Benefits of technology

This achievement enables controllable thickness of graphene thermal conductive films, improving thermal conductivity and product stability, and ensuring the reliability of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120987303A_ABST
    Figure CN120987303A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a graphene heat-conducting film. The preparation method mainly comprises the following steps: preparing graphene oxide slurry, coating the graphene oxide slurry to form graphene oxide films, laminating the graphene oxide films, carrying out pressurized heat treatment, and calendering to obtain the graphene heat-conducting film. By regulating and controlling the raw materials of the graphene oxide slurry, the median particle size of the slurry, the heat treatment process and other process parameters and methods, the thermal diffusion coefficient of the heat-conducting film is improved, and the industrial production of the product is more stable and reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of graphene preparation technology, specifically to a graphene thermal conductive film and its preparation method. Background Technology

[0002] Graphene has a wide range of applications due to its unique structure and properties, such as high electrical conductivity, high strength, and high thermal conductivity. In particular, thermal conductive films are widely used because of their excellent thermal conductivity.

[0003] The main method for industrial-scale preparation of graphene thermal conductive films is the redox method. During this process, multiple factors, including the selection of raw materials, process parameters, and thermal reduction conditions, all affect the thermal conductivity of the graphene thermal conductive film. Furthermore, as a mass-produced industrial product, the yield and size of graphene thermal conductive films must be controllable. During the thermal reduction process, the graphene thermal conductive film undergoes self-assembly by removing functional groups. Simultaneously, the removed functional groups are released as gases such as water, carbon dioxide, and carbon monoxide. This gas release leads to a "thermal expansion" phenomenon, increasing the film thickness, which poses a challenge to controlling the product's size. Summary of the Invention

[0004] In view of one or more of the problems existing in the prior art, the present invention provides a graphene thermal conductive film and a method for preparing the same.

[0005] In a first aspect, a method for preparing a graphene thermally conductive film is provided, comprising the following steps: A graphene oxide slurry is prepared, wherein the graphene oxide slurry is composed of a solvent and a solute, wherein the solute includes graphene oxide, and the solvent includes one or more of deionized water, ammonia, DMF, NMP, ethanol, and isopropanol. Graphene oxide slurry is coated into a graphene oxide film; Graphene oxide films are stacked and subjected to pressure heat treatment, followed by calendering to obtain a graphene thermally conductive film.

[0006] During the heat treatment of graphene oxide film, the removal of functional groups releases a large amount of gas, causing the film material to expand dramatically in volume. Without pressure, it will expand several times in the height direction of the film material, and the expansion coefficient is uncontrollable, resulting in an uncontrollable thickness of the final graphene thermal conductive film.

[0007] In a further technical solution, the load-bearing pressure of the graphene oxide film is 196N~490N. Wherein, the load-bearing pressure F=mg, m is the mass of the load, and g is the gravitational constant, taken as g=9.8N / kg.

[0008] In a further technical solution, the pressure heat treatment includes pressure pretreatment at 150-380℃, pressure carbonization at 900-1400℃, and pressure graphitization at 2000-3300℃.

[0009] Segmented heat treatment avoids excessive gas generation during rapid thermal reduction of the graphene film. The rapid gas generation and discharge of gas across the cross-section of the graphene film can easily tear its internal structure, reducing its long-range order and hindering thermal conductivity; in severe cases, it can even lead to furnace explosion and scrapping. Segmented heat treatment, on the other hand, primarily removes moisture and a small amount of oxygen-containing functional groups in the pretreatment stage, removes most of these functional groups in the carbonization stage, and almost completely removes them in the graphitization stage. Simultaneously, various defects are repaired, improving the intrinsic thermal conductivity of graphene.

[0010] In a further technical solution, during the pressure pretreatment and / or pressure carbonization and / or pressure graphitization processes, a layer of graphite paper is intercalated between the stacked single or multiple sheets of graphene oxide films. The graphite paper can be the same size as the graphene oxide film or much smaller; the size of the graphite paper is not specifically required.

[0011] During heat treatment, especially during carbonization and graphitization, high temperatures cause the organic components in graphene oxide to undergo pyrolysis and condensation reactions, leading to carbon atom rearrangement and the formation of a more stable carbon structure. Simultaneously, oxygen-containing functional groups on the surface of the graphene oxide film may undergo esterification and dehydration reactions at high temperatures, thereby enhancing the bonding force between the two graphene oxide films. Even without chemical reactions, the two graphene oxide films may bond together through physical adsorption and van der Waals forces. Although these forces are relatively weak, they can be strengthened during carbonization and graphitization due to the close arrangement of the carbon structures. For these reasons, adhesion can occur between adjacent graphene films during heat treatment. The intercalation of graphite paper can reduce this adhesion, improve subsequent film peeling efficiency, and prevent film damage during separation.

[0012] The interlayer spacing of graphite paper is determined by the thickness of the single-layer graphene oxide film and the required thickness of the graphene thermal conductive film.

[0013] In a further technical solution, the solute of the graphene oxide slurry also includes polyimide, with the mass fraction of graphene oxide being 3-10% and the mass fraction of polyimide being 0.1-3%.

[0014] There is a strong π-π interaction between the aromatic ring of polyimide and the aromatic structure of graphene oxide, which allows them to approach each other and form a stable structure. At the same time, the molecular structure of polyimide contains imide groups and amine groups, which can form hydrogen bonds with other polyimide molecules or different materials. Through the above bridging connection, the gaps and defects between graphene thermal conductive films can be reduced, and the overall performance of the thermal conductive film can be improved.

[0015] The amount of polyimide added should be greater than 0.1%. Insufficient polyimide addition will not improve the thermal conductivity. The amount of conventional polyimide added should be less than 2%. Since graphene oxide slurry is water-based, and conventional polyimide is not hydrophilic, if too much polyimide is added, it cannot be uniformly dispersed in the water-based graphene oxide slurry system to participate in self-assembly. Of course, in a further scheme, hydrophilic modified water-soluble polyimide can be selected for addition, but the amount of water-soluble polyimide added should also be controlled to be less than 3%. The polyimide remaining after the self-assembly reaction will exist in the form of residual carbon between graphene sheets after heat treatment, which will lead to an increase in the interlayer spacing of graphene, which is not conducive to the transmission of phonons, thereby reducing the thermal conductivity of the graphene film. In a further technical solution, the viscosity of the graphene oxide slurry is ≥4000cp. If the viscosity is <4000cp, the slurry has a large fluidity, which is easy to exceed the allowable error range of the designed coating thickness. It is not feasible to use experimental design and it is impossible to coat a thick film.

[0016] In a further technical solution, the solute in the graphene oxide slurry also includes flake graphite to increase the longitudinal heat conduction channels.

[0017] In a further technical solution, the mass fraction of flake graphite is 5%-15%.

[0018] In a further technical solution, the degree of oxidation of graphene oxide and the median particle size of the solute follow the following rules: when the CO peak in the XPS test of graphene oxide is ≥ the CC peak, the median particle size of the solute is ≤ 1 μm; and / or, when the CO peak in the XPS test of graphene oxide is < the CC peak, 1 μm < the median particle size of the solute is ≤ 10 μm.

[0019] In other words, the rule that the smaller the solute sheet diameter, the higher the film thermal conductivity applies to graphene oxide with a high degree of oxidation (CO peak > CC peak in XPS spectrum). This is because, even after the sheet diameter of graphene oxide with a high degree of oxidation of the solute material is reduced, the graphene oxide fragments still contain certain oxygen-containing functional groups. The self-assembly process can achieve chemical bonding between adjacent graphene oxide sheets and polyimide sheets. In the aqueous phase, graphene oxide mainly exists in three conformations: planar, wrinkled, entangled, and folded. The latter three conformations are not conducive to the macroscopic self-assembly of graphene oxide films (wrinkled, entangled, and folded conformations easily form microcapsule structures). After homogenization control reduces the overall sheet diameter of the solute, the sheet diameter of graphene oxide, one of the solute materials, is also reduced. This can reduce the proportion of the latter three conformations of graphene oxide sheets and increase the planar proportion of graphene oxide sheets, so that the graphene oxide sheets coated with graphene oxide films exist in a planar conformation (similar to liquid crystal), which is beneficial to self-assembly and improved thermal conductivity. Specifically, for graphene oxide with a high degree of oxidation (CO peak > CC peak in XPS spectrum), the median particle size of the solute should be controlled to ≤1μm; Conversely, the rule that larger solute flake diameters lead to higher film thermal conductivity applies to low-oxidation graphene oxide (XPS spectrum CO peak < CC peak). This is because, as the flake diameter of low-oxidation graphene oxide becomes smaller, the low-oxidation graphene fragments carry only a small number or no oxygen-containing functional groups. This makes it difficult to achieve perfect chemical bonding between adjacent graphene oxide flakes and polyimide flakes during self-assembly. Furthermore, a large number of hanging (or pore) defects are introduced between the graphene oxide fragments, resulting in lower thermal conductivity (SP) of the thermally conductive film. 2 The long-range order of hybridization is disrupted, and phonon transport is significantly scattered at the edge defects of graphene fragments, leading to a decrease in thermal conductivity. Therefore, for low oxidation levels (CO peak < CC peak in XPS spectra), the solute needs to maintain a certain flake size (1 μm < median particle size ≤ 10 μm) to reduce defect introduction and improve thermal conductivity. Preferably, when the CO peak < CC peak in the XPS test of graphene oxide, the median particle size of the solute should be 1.5 μm ≤ 10 μm.

[0020] A second aspect of the present invention provides a graphene thermally conductive film prepared by any or a combination of the above-described schemes.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The graphene thermal conductive film prepared by the technical solution described in this invention has an improved thermal diffusivity through improvements in process parameters and raw material selection. Furthermore, the process improvements in this solution make the industrial production of the product more stable and reliable. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 XPS test image of the graphene oxide cake used in Example 1; Figure 2 This is a test graph of the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 1; Figure 3 This is a test graph of the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 2; Figure 4 This is a graph showing the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 3. Figure 5 This is a graph showing the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 4. Figure 6 This is a graph showing the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 5. Figure 7 The graph shows the horizontal thermal diffusivity test result of the graphene thermally conductive film prepared in Example 6. Figure 8 XPS test image of the graphene oxide cake used in Example 7; Figure 9 This is a test graph of the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 7; Figure 10 The graph shows the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 8. Figure 11 The graph shows the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 9. Figure 12 This is a test graph of the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 10; Figure 13 This is a graph showing the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 11. Figure 14 This is a graph showing the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Example 12. Figure 15 The graph shows the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Comparative Example 1. Figure 16 The graph shows the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Comparative Example 2. Figure 17The graph shows the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Comparative Example 3. Figure 18 The graph shows the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Comparative Example 4. Figure 19 The graph shows the horizontal thermal diffusivity of the graphene thermally conductive film prepared in Comparative Example 5. Detailed Implementation

[0024] The following detailed description of exemplary embodiments of the invention refers to the accompanying drawings, which form part of the description, illustrating exemplary embodiments in which the invention may be practiced, wherein features of the invention are identified by reference numerals. The more detailed description of embodiments of the invention below is not intended to limit the scope of the claimed invention, but is merely illustrative and not to limit the description of the features and characteristics of the invention, to suggest the best mode for carrying out the invention, and is sufficient to enable those skilled in the art to practice the invention. However, it should be understood that various modifications and variations can be made without departing from the scope of the invention as defined by the appended claims. The detailed description and drawings should be considered illustrative only and not restrictive, and any such modifications and variations will fall within the scope of the invention described herein. Furthermore, the background art is intended to illustrate the current state of research and development and significance of the technology, and is not intended to limit the invention or the application field of the invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention; the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0026] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0027] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0028] In the following detailed embodiments and comparative examples: The method for testing the solid content of graphene oxide cake is as follows: First, weigh the mass of the exfoliated culture dish and record it as m1; place the wet cake to be tested into the exfoliated culture dish and record it as m2, where the mass of the wet cake is m2-m1; transfer the culture dish containing the wet cake to a forced-air drying oven at 40℃-90℃ and record the mass of the cake + the exfoliated culture dish as m3; at this point, if the mass of the cake no longer changes, it is considered that all the moisture in the wet cake is ash, and the cake is a dry cake; calculate the solid content of the cake as (m3-m1) / (m2-m1), and record the data in percentage form; to ensure the accuracy of the data, measure 3-5 sets of cakes and take the average value; to reduce the error of the data, the mass of one wet cake should be ≥3g, preferably 10-20g / set; to ensure that the moisture evaporates during the drying process, the cake should exist in the form of small particles or flat and thin, such as by flattening or sieving.

[0029] The XPS test method is as follows: An ESCA lab 250 XPS tester is used, with the sample subjected to a base pressure of 3 × 10⁻⁶. -8 In the Pa energy analysis mode, X-rays of Al Ka ​​1486.8 eV were used as the excitation source to test the chemical composition of the sample.

[0030] The oxygen content of the feed cake was tested using XPS.

[0031] The median particle size was measured directly using a laser particle size analyzer.

[0032] The test method for the horizontal thermal diffusivity is as described in standard QGDMR 04-2023, "Laser flash method for testing thermal conductivity".

[0033] The test method for the vertical thermal diffusivity is as described in standard GB / T 22588-2008, "Measuring Thermal Diffusivity or Thermal Conductivity by Flash Method". Example 1

[0034] S1. Purchase A52 type graphene oxide cake from Yuntian Morui. Take 50g and flatten it in a glass petri dish. Dry it in a 78°C forced-air oven until the mass no longer changes and calculate the solid content of the graphene oxide cake to be 48.90%. Take another 50g of A52-1 type graphene oxide cake and pass it through a 100-mesh sieve to obtain a fine graphene oxide cake. Dry it in a 78°C forced-air oven and then grind it through a 150-mesh sieve to obtain graphene oxide powder. Perform XPS characterization tests on the obtained graphene oxide powder to obtain... Figure 1 The XPS spectrum shown indicates that the CO peak intensity is significantly stronger than the CC peak intensity. S2. Weigh 1.25 kg of the graphene oxide cake from step S1. Using water as a solvent, add ammonia to adjust the pH of the solution to 6, and prepare a graphene oxide slurry with a solid content of 5% and a viscosity of 15000 cp. At the same time, add 5% by mass of flake graphite and 1% by mass of water-soluble polyimide powder. Disperse the slurry using a planetary mixer with a stirring speed of 100 r / min, a dispersion speed of 3000 r / min, and a working time of 3 h. Then, homogenize the composite slurry, and adjust its particle size D50 value to 0.581 μm. Finally, perform a defoaming operation to obtain the target graphene oxide slurry.

[0035] S3. Coat the target graphene oxide slurry to a thickness of 5 mm and dry it in a low humidity atmosphere to obtain a graphene oxide film.

[0036] S4. Graphene oxide films are stacked and separated by graphite paper. The graphite paper is inserted at one corner of the edge of the graphene oxide film. The film is pretreated at 260°C for 1 hour, carbonized at 1200°C for 1 hour in a nitrogen atmosphere, and graphitized at 2900°C for 1 hour in an argon atmosphere. All the pretreatment, carbonization and graphitization are carried out under a pressure of 343N. Finally, the target graphene thermal conductive film is obtained by flat pressing.

[0037] The horizontal thermal diffusivity of the graphene thermally conductive film was measured to be 922.389 mm. 2 / s, longitudinal thermal diffusivity is 17.373 mm 2 / s. Its horizontal thermal diffusivity test graph is shown below. Figure 2 As shown. Example 2-3

[0038] Unlike Example 1, in step S2, the mass fractions of the added polyimide powder were 0.3% and 3%, respectively, and the particle size D50 control values ​​were 0.461 μm and 0.592 μm, respectively. All other steps were consistent with Example 1.

[0039] The measured horizontal thermal diffusivity of the graphene thermally conductive film was 845.076 mm. 2 / s, 850.844 mm 2 / s; the longitudinal thermal diffusivity is 14.226 mm. 2 / s, 14.351 mm 2 / s. The horizontal thermal diffusivity test graphs for Examples 2-3 are shown below. Figure 3-4 As shown. Examples 4-6

[0040] Unlike Example 1, in step S2, the mass fractions of the added flake graphite were 0%, 10%, and 15%, respectively, and the controlled values ​​of their particle size D50 were 0.398 μm, 0.468 μm, and 0.864 μm, respectively. All other steps were consistent with those in Example 1.

[0041] The horizontal thermal diffusivity of the graphene thermally conductive film was measured to be 897.048 mm. 2 / s, 916.053 mm 2 / s, 804.469 mm 2 / s; the longitudinal thermal diffusivity is 9.359 mm. 2 / s, 16.279 mm 2 / s, 13.199 mm 2 / s. The horizontal thermal diffusivity test graphs for Examples 4-6 are shown below. Figure 5-7 As shown. Example 7

[0042] Unlike Example 1, the selection of graphene oxide cake in step S1 is different, and the particle size control in step S2 is also different. The specific preparation method of the graphene thermal conductive film in Example 7 is as follows: S1. Take another batch of graphene oxide cake, take 50g and flatten it in a glass petri dish. Dry it in a 78°C forced-air oven until the mass no longer changes and calculate the solid content of the graphene oxide cake to be 46.75%. Take another 50g of graphene oxide cake and pass it through a 100-mesh sieve to obtain fine graphene oxide cake. Dry it in a 78°C forced-air oven and then grind it through a 150-mesh sieve to obtain graphene oxide powder. Perform XPS characterization tests on the obtained graphene oxide powder to obtain... Figure 8 The XPS spectrum shown shows that the CO peak intensity is significantly weaker than the CC peak intensity. S2. Weigh 1.25 kg of the graphene oxide cake from step S1. Using water as a solvent, add ammonia to adjust the pH of the solution to 6, and prepare a graphene oxide slurry with a solid content of 5% and a viscosity of 15000 cp. At the same time, add 5% by mass of flake graphite and 1% by mass of water-soluble polyimide powder. Disperse the slurry using a planetary mixer with a stirring speed of 100 r / min, a dispersion speed of 3000 r / min, and a working time of 3 h. Then, homogenize the composite slurry, and adjust its particle size D50 value to 4.156 μm. Finally, perform defoaming to obtain the target graphene oxide slurry.

[0043] S3. Coat the target graphene oxide slurry to a thickness of 5 mm and dry it in a low humidity atmosphere to obtain a graphene oxide film.

[0044] S4. Graphene oxide films are stacked and separated by graphite paper. The films are pretreated at 260°C for 1 hour, carbonized at 1200°C for 1 hour in a nitrogen atmosphere, and graphitized at 2900°C for 1 hour in an argon atmosphere. All the pretreatment, carbonization and graphitization are carried out under a pressure of 343N. Finally, the target graphene thermal conductive film is obtained by flat pressing.

[0045] The horizontal thermal diffusivity of the graphene thermally conductive film was measured to be 909.816 mm. 2 / s, longitudinal thermal diffusivity is 16.015 mm 2 / s. The horizontal thermal diffusivity test graph for Example 7 is shown below. Figure 9 As shown. Example 8

[0046] Unlike Example 7, the particle size of the graphene oxide cake dispersion slurry was controlled to D50 = 1.569 μm. All other steps and process parameters were the same as in Example 7. The purpose was to explore the effect of particle size control on the thermal conductivity of the graphene thermal conductive film.

[0047] The horizontal thermal diffusivity of the graphene thermally conductive film was measured to be 882.303 mm. 2 / s, longitudinal thermal diffusivity is 16.854 mm 2 / s. The horizontal thermal diffusivity test graph for Example 8 is shown below. Figure 10 As shown. Examples 9-10

[0048] Unlike Example 1, in step S4, the pretreatment, carbonization and graphitization were performed under pressures of 196 N and 490 N, respectively, while the other steps were consistent with those in Example 1.

[0049] The horizontal thermal diffusivity of the graphene thermally conductive film was measured to be 856.752 mm. 2 / s, 863.045 mm 2 / s; the longitudinal thermal diffusivity is 16.435 mm. 2 / s, 15.917 mm 2 / s. The horizontal thermal diffusivity test graphs for Examples 9-10 are shown below. Figure 11-12 As shown. Example 11

[0050] Unlike Example 1, in step S2, the viscosity of the graphene oxide slurry was set to 4000 cp, while the other steps remained the same as in Example 1.

[0051] The horizontal thermal diffusivity of the graphene thermally conductive film was measured to be 833.373 mm. 2 / s, longitudinal thermal diffusivity is 11.292 mm 2 / s. The horizontal thermal diffusivity test graph for Example 11 is shown below. Figure 13 As shown. Example 12

[0052] Unlike Example 1, in step S4, graphite paper is used to separate every 3 layers of film; all other steps are consistent with Example 3.

[0053] The horizontal thermal diffusivity of the graphene thermally conductive film was measured to be 908.083 mm. 2 / s, longitudinal thermal diffusivity is 12.562 mm 2 / s. The graphene thermally conductive films not separated by graphite paper adhered to each other and were difficult to separate, resulting in a final graphene thermally conductive film thickness three times that of the film in Example 1. The horizontal thermal diffusivity test graph for Example 12 is shown below. Figure 14 As shown.

[0054] The graphene thermally conductive films obtained in Examples 1-3 and 5-12 have a horizontal thermal diffusivity ≥800 mm. 2 / s, longitudinal thermal diffusivity ≥10mm 2 / s Comparative Example 1

[0055] Unlike Example 1, this comparative example differs in that the particle size of the graphene oxide cake dispersion slurry is controlled to D50 = 1.361 μm in step S2. All other steps and process parameters are the same as in Example 1. The purpose is to investigate the effect of non-optimal particle size control on the thermal conductivity of the graphene thermal conductive film. The results show that the horizontal thermal diffusivity of the graphene oxide thermal conductive film obtained in Comparative Example 1 is 736.201 mm. 2 / s, significantly lower than in Example 1, is attributed to the presence of numerous graphene oxide sheet conformations such as wrinkles, overlaps, and entanglements that are detrimental to thermal conductivity in the graphene oxide film at this particle size. The horizontal thermal diffusivity test graph for Comparative Example 1 is shown below. Figure 15 As shown. Comparative Example 2

[0056] The difference between this comparative example and Example 7 is that the particle size of the graphene oxide cake dispersion slurry was controlled to D50 = 0.418 μm in step S2. All other steps and process parameters were the same as in Example 7. The purpose was to investigate the effect of non-optimal particle size control on the thermal conductivity of the graphene thermal conductive film. The results showed that the horizontal thermal diffusivity of the graphene oxide thermal conductive film obtained in Comparative Example 4 was 724.039 mm. 2The thermal diffusivity of the graphene film at this particle size is significantly lower than that in Example 7. This is attributed to the fact that the graphene sheets in the graphene film at this particle size do not carry enough oxygen-containing groups. Many graphene fragments without oxygen-containing groups cannot participate in the self-assembly reaction, introducing a large number of edge defects that cannot be completely repaired during the graphitization stage, resulting in a low thermal diffusivity of the obtained graphene thermally conductive film. The horizontal thermal diffusivity test graph of Comparative Example 2 is shown in the figure below. Figure 16 As shown. Comparative Example 3

[0057] The difference between this comparative example and Example 7 is that the particle size of the graphene oxide cake dispersion slurry was controlled to D50 = 12.108 μm in step S2. All other steps and process parameters were the same as in Example 7. The purpose was to investigate the effect of non-optimal particle size control on the thermal conductivity of the graphene thermal conductive film. The results showed that the horizontal thermal diffusivity of the graphene oxide thermal conductive film obtained in Comparative Example 5 was 712.362 mm. 2 The thermal diffusivity of the graphene thermal conductive film obtained in Example 7 is significantly different from that of the film obtained in Example 7. This is attributed to the presence of numerous graphene oxide conformations such as wrinkles, overlaps, and entanglements at this particle size, which are detrimental to thermal conductivity. These conformations form numerous microcapsules and voids in the graphene thermal conductive film, hindering the improvement of its thermal conductivity. The horizontal thermal diffusivity test graph of Comparative Example 3 is shown below. Figure 17 As shown. Comparative Example 4

[0058] Unlike Example 1, in step S2, the mass fraction of the added polyimide powder is 0.05%, while the other steps are consistent with Example 1.

[0059] Test results show that the horizontal thermal diffusivity of the graphene thermally conductive film sample obtained in this comparative example is 767.074 mm. 2 The decrease in the horizontal thermal diffusivity ( / s) is attributed to insufficient addition of water-soluble polyimide, resulting in a low degree of participation in the self-assembly reaction and an inability to effectively act as a bridging link, thus degrading the thermal conductivity of the graphene composite film. The horizontal thermal diffusivity test graph for Comparative Example 4 is shown below. Figure 18 As shown. Comparative Example 5

[0060] Unlike Example 1, in step S2, the mass fraction of the added polyimide powder is 3.5%, while the other steps are consistent with Example 1.

[0061] Test results show that the horizontal thermal diffusivity of the graphene thermally conductive film sample obtained in this comparative example is 716.075 mm. 2The figure / s is attributed to the excessive addition of polyimide. The remaining polyimide from the self-assembly reaction, after graphitization, exists as residual carbon between graphene layers, leading to increased interlayer spacing, which is detrimental to phonon transport and thus reduces the thermal conductivity of the graphene film. The horizontal thermal diffusivity test graph for Comparative Example 5 is shown below. Figure 19 As shown. Comparative Example 6

[0062] Unlike Example 1, in step S2, the viscosity of the graphene oxide slurry was set to 3500 cp, while all other steps remained the same as in Example 1. The graphene slurry could not be coated into a film due to its low viscosity. Comparative Example 7

[0063] Unlike Example 1, in step S4, the heat treatment of the graphene oxide film is not carried out under pressure. The thermal expansion of the graphene oxide film during the heat treatment process is not limited, and the thickness of the sintered graphene film is uneven. The thickness difference between different graphene thermal conductive films is ≥15μm, and the thickness difference between different parts of a single graphene thermal conductive film is ≥10μm. Comparative Example 8

[0064] The difference between this comparative example and Example 1 is that in step S4, the reduced graphene oxide film was directly graphitized at 2900°C. Ultimately, due to the large amount of gas released simultaneously during the heat treatment, the reduced graphene oxide film directly broke and burned.

[0065] In the above embodiments, the descriptions of each embodiment have different focuses. For parts that are not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.

[0066] The above description describes specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a graphene thermally conductive film, characterized in that the steps include... include: A graphene oxide slurry is prepared, wherein the graphene oxide slurry is composed of a solvent and a solute, wherein the solute includes graphene oxide, and the solvent includes one or more of deionized water, ammonia, DMF, NMP, ethanol, and isopropanol. Graphene oxide slurry is coated into a graphene oxide film; Graphene oxide films are stacked and subjected to pressure heat treatment, followed by calendering to obtain a graphene thermally conductive film.

2. A method for preparing a graphene thermally conductive film as described in claim 1, characterized in that, The solute in the graphene oxide slurry also includes polyimide, with the mass fraction of graphene oxide being 3-10% and the mass fraction of polyimide being 0.1-3%.

3. A method for preparing a graphene thermally conductive film as described in claim 2, characterized in that, The viscosity of the graphene oxide slurry is ≥4000cp.

4. A method for preparing a graphene thermally conductive film as described in any one of claims 1-3, characterized in that, The solute in graphene oxide slurry also includes flake graphite.

5. A method for preparing a graphene thermally conductive film as described in claim 4, characterized in that, The mass fraction of the flake graphite is 5%-15%.

6. A method for preparing a graphene thermally conductive film as described in claim 1, characterized in that, The degree of oxidation of the graphene oxide and the median particle size of the solute follow the following rules: When the CO peak is greater than or equal to the CC peak in the XPS test of graphene oxide, the median particle size of the solute is ≤1μm. And / or, when the CO peak < CC peak in the XPS test of graphene oxide, 1 μm < median particle size of the solute ≤ 10 μm, preferably, when the CO peak < CC peak in the XPS test of graphene oxide, 1.5 μm ≤ median particle size of the solute ≤ 10 μm.

7. A method for preparing a graphene thermally conductive film as described in claim 1, characterized in that, During the pressurized heat treatment process, the load pressure on the graphene oxide film is 196N~490N.

8. A method for preparing a graphene thermally conductive film as described in claim 1, characterized in that, The pressure heat treatment includes pressure pretreatment at 150-380℃, pressure carbonization at 900-1400℃, and pressure graphitization at 2000-3300℃.

9. A method for preparing a graphene thermally conductive film as described in claim 8, characterized in that, During pressure pretreatment and / or pressure carbonization and / or pressure graphitization, graphite paper is intercalated between stacked single or multiple sheets of graphene oxide films.

10. A graphene thermally conductive film, characterized in that, Prepared by the method described in any one of claims 1 to 9.